Prognostic value of radiographic extracapsular extension in locally advanced head and neck squamous cell cancers. (January 2016) - Liu, Jerry T.; Kann, Benjamin H.; De, Brian; Buckstein, Michael; Bakst, Richard L.; Genden, Eric M.; Posner, Marshall R.; Som, Peter M.; Gupta, Vishal
Highlights: Pretreatment neck CTs were reviewed for 258 LAHNC patients who completed EBRT. One-hundred forty patients (54%) were rECE-positive and 118 (46%) rECE-negative. Presence of rECE independently predicts for worse OS, PFS, DC, and LRC for all LAHNC except HPV-positive LAOPC. Summary: Objectives: We investigated associations between radiographic evidence of nodal extracapsular extension (rECE) and outcomes for locally advanced head and neck squamous cell cancers (LAHNC). Materials and methods: We conducted a single-institution retrospective study of 258 consecutive LAHNC patients with accessible pretreatment contrast-enhanced neck CT scans, who completed definitive or adjuvant radiation therapy. All scans were reviewed by an expert head and neck radiologist for evidence of rECE. Kaplan–Meier and Cox regression multivariate analyses (MVA) were performed to evaluate the impact of rECE on overall survival (OS), progression free survival (PFS), distant control (DC), and locoregional control (LRC). Results: One-hundred forty patients were rECE-positive and 118 were rECE-negative. The rECE-positive cohort had more cN3 disease (11.6% vs. 0.8%) and heavier smoking histories (60.0% vs. 44.9% with ⩾10-pack-years). The rECE-positive cohort had significantly worse 3-year OS (64.3% vs. 82.8%, p  = 0.002), PFS (58.9% vs. 76.0%, p  = 0.001), DC (72.3% vs. 90.6%, p  < 0.001), and LRC (75.9% vs. 89.8%, p  = 0.002). On MVA, rECE independently predicted for worse OS, PFS, DC, and LRC for LAHNC overall. On subset analysis of HPV-positive oropharyngeal cancers, rECE was not a significant prognosticator. Conclusion: For all sites of LAHNC, except HPV-positive oropharyngeal cancers, presence of rECE independently predicts for worse disease control and survival. Further studies are needed to validate these findings and demonstrate whether rECE may be considered for risk-stratifying patients for clinical trial design and treatment decisions.